2011
DOI: 10.1371/journal.pntd.0001242
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic Filariasis: A Method to Identify Subclinical Lower Limb Change in PNG Adolescents

Abstract: Lymphedema related to lymphatic filariasis (LF) is a disabling condition that commonly manifests in adolescence. Fifty-three adolescents, 25 LF infected and 28 LF non-infected, in age and sex-matched groups, using the Binax ICT rapid card test for filarial antigen were recruited to the study. None of the participants had overt signs of lymphedema. Lymphedema assessment measures were used to assess lower limb tissue compressibility (tonometry), limb circumference (tape measure), intra- and extra-cellular fluid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…Intrarater reliability ranged from 0.88 -0.99. (11,32,33) In upper extremities, for the subgroup with lymphedema ICC was 0.95 and without lymphedema 0.81. (32) Pooled ICCintra for lower extremities showed an ICC of 0.89 (95%CI 0.88 -0.90).…”
Section: Reliabilitymentioning
confidence: 99%
See 4 more Smart Citations
“…Intrarater reliability ranged from 0.88 -0.99. (11,32,33) In upper extremities, for the subgroup with lymphedema ICC was 0.95 and without lymphedema 0.81. (32) Pooled ICCintra for lower extremities showed an ICC of 0.89 (95%CI 0.88 -0.90).…”
Section: Reliabilitymentioning
confidence: 99%
“…In five studies the included patients were both female and male. (11,(20)(21)(22)(23) <<Insert figure 1 about here>> Fifteen studies reported reliability using ICC; SEM was reported in nine studies and SDC in two studies. Concurrent validity was reported in 16 studies, convergent validity in eight studies.…”
Section: Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations